Internet exposure and knowledge of HIV/AIDS among adolescents in India: exploring the mediating role of self-efficacy using UDAYA data - Prinitha, Sridhar; Jose, Tony P. (Frontiers in Communication, 2025)
IntroductionIn culturally conservative environments, adolescents are more likely to seek sexual health information from the internet, where traditional channels of communication are hindered. However, mere exposure to the internet does not directly translate into knowledge, as this relationship is shaped by critical individual factors, such as adolescents’ self-efficacy and functional digital health literacy.ObjectiveThe present study investigates the relationship between internet exposure and HIV/AIDS knowledge among Indian adolescents, specifically examining the mediating role of self-efficacy and the moderating role of functional digital health literacy.MethodsData for this study were drawn from Wave 2 (2018–19) of the Understanding the Lives of Adolescents and Young Adults (UDAYA) survey. The final sample included 6,103 adolescents (n = 2,159 males; n = 3,944 females). Statistical analyses included Spearman’s rank-order correlation, mediation and moderated mediation analysis using Hayes’ PROCESS macro.ResultsCorrelational analysis showed that internet exposure was positively associated with HIV/AIDS knowledge (r = 0.21, p < 0.001). Mediation analysis revealed that self-efficacy significantly mediated this relationship (Bindirect = 0.004, 95% CI: 0.001, 0.007), accounting for 4.8% of the total effect. Moderated mediation analysis further demonstrated that this mediation effect was conditional on functional digital health literacy levels (Index = 0.01, 95% CI: 0.003, 0.02).ConclusionThe findings indicate that self-efficacy acts as the mediator between internet exposure and HIV/AIDS knowledge, with functional digital health literacy moderating this process. Policymakers should incorporate comprehensive digital health literacy elements and self-efficacy enhancement strategies into current health education modules in order to maximize knowledge acquisition and intervention impact.